The synthesis of a novel molecular imaging probe 68Ga-DOTA-PDL1P and application in mouse model of melanoma - YANG Ziyi, LI Panli, GU Bingxin, LIU Cheng, SONG Shaoli, XU Xiaoping (Zhongguo aizheng zazhi, 2023)
Background and purpose: The immunogenic drugs represented by programmed cell death 1 (PD-1) and programmed death ligand-1 (PD-L1) have achieved great success in clinic. However, with the development of clinical application, the overall effective rate varies greatly. At present, detection of the expression of PD-1/PD-L1 before the start of tumor treatment is an important basis for clinical medication. However, the current detection method of PD-L1 expression requires the acquisition of patient specimens, which is traumatic. Therefore, there is an urgent need to develop a noninvasive method to detect PD-L1 expression in vivo. This study innovatively designed and synthesized a new positron emission tomography (PET) imaging agent targeting PD-L1 polypeptide 68Ga-DOTA-PDL1P. In this study, the labeling rate, radiochemical purity and stability of 68Ga-DOTA-PDL1P were evaluated for quality control. And the application was evaluated in the mouse model of melanoma in order to obtain a promising 68Ga-DOTA-PDL1P immune PET probe. Methods: Gallium-68 (68Ga) was used to label DOTA-PDL1P, and its radiochemical purity and stability were evaluated by quality control. To evaluate its specific targeting performance, the cell uptake and blocking experiments were carried out in murine melanoma B16-F10 cells. The biodistribution experiment was performed in B16-F10 tumor-bearing mice to analyze the metabolism of the PET imaging agent in vivo. The Tumor uptake of 68Ga-DOTA-PDL1P in B16-F10 tumor-bearing mice was observed by PET/CT imaging, and the tumor/muscle (T/M) ratio was semi-quantitatively analyzed. In addition, radioautography was performed to further analyze the tumor uptake of 68Ga-DOTA-PDL1P probe. Tumor cell proportion score (TPS) and combined positive score (CPS) were used to analyze the immunohistochemical staining results to evaluate the expression of PD-L1 in tumor tissues. Results: The labeling efficiency and radiochemical purity of 68Ga-DOTA-PDL1P were more than 99%, and the radiochemical purity of 68Ga-DOTA-PDL1P was more than 90% after 3 h of incubation in PBS and fetal bovine serum. Cellular uptake results showed that 68Ga-DOTA-PDL1P could be specifically taken up by B16-F10 cells, and the specific uptake could be blocked by PD-L1P peptide competitive binding. Biodistribution assay showed that 68Ga-DOTA-PDL1P was mainly excreted through the urinary system. The results of microPET/CT imaging of tumor-bearing mice showed a high uptake of 68Ga-DOTA-PDL1P in tumor tissues, and the T/M ratio was 6.7. The autoradiography results confirmed that 68Ga-DOTA-PDL1P high uptake in the tumor was consistent with the PD-L1 positive area of immunohistochemical staining, which proved that 68Ga-DOTA-PDL1P could specifically bind to PD-L1 positive malignant tumor cells. Conclusion: The novel 68Ga-DOTA-PDL1P PET imaging agent synthesized in this study has good stability and can specifically target PD-L1 positive tumor cells, which is a promising new immune PET probe targeting PD-L1 protein.